Cultural Festival As A Salient Tool For Strategic, Holistic And Sustainable Rural Development In Africa: The Case Of The Opemso) Festival Of The Asantes Of Ghana - Adom, Dickson (Advances in Social Sciences Research Journal, 2016)
The Opemso) cultural festival is one of the iconic cultural festivals among the Asante ethnic society in Ghana. It is historically and culturally charged, glued to the beginnings of the most vibrant Asante kingdom because of its affiliation to the birth of the founder, Otumfuo Osei Tutu I. Using qualitative approaches, the researcher accentuates the immense contributions of the festival to the cultural, historical, social and economic development of the people of Anyinam and Kokofu in the Ashanti region of Ghana. Semi-structured interviews as well as direct observations were the main instruments for the collection of rich data on the great significance of the festival in the lives of residents and visitors from respondents who were purposively and randomly sampled. The data were qualitatively analyzed using the Data analysis spiral method to interpret the archetypal roles that the Opemso) cultural festival plays in the everyday life of the people. The study contends that if cultural festivals are strategically planned and well tailored in line with developmental policies and ideologies of a society or nation at large, they can be salient tools for the development of rural areas especially in festival-prone nations in Sub-Sahara Africa.